Math Problems

## Questions

 $$y = 4 x^2$$ $$y = x^2 + 5 x$$ $$y = 2 x^2 + 6 x$$ $$y = 2 x^2 -9 x + 9$$ $$y = 3 x^2 -7 x -6$$ $$y = 4 x^2 -x$$ $$y = x^2 -3 x -10$$ $$y = x^2 + 3 x$$ $$y = x^2 -6 x + 8$$ $$y = x^2 + 7 x + 10$$ $$y = 2 x^2 + 3 x$$ $$y = x^2 + 8 x + 15$$ $$y = 2 x^2 -2 x$$ $$y = 4 x^2 + x -3$$ $$y = 4 x^2 -8 x$$ $$y = x^2 + 4 x -5$$ $$y = x^2 -4 x -5$$ $$y = 3 x^2 + 8 x -3$$ $$y = 2 x^2$$ $$y = x^2 -2 x -15$$ $$y = x^2 + 5 x + 6$$ $$y = x^2 -8 x + 15$$ $$y = 3 x^2 -2 x$$ $$y = 4 x^2 -x -3$$ $$y = x^2 -5 x + 4$$ $$y = 2 x^2 -3 x -2$$ $$y = x^2 + x -20$$ $$y = x^2 + 4 x -5$$

 $$y = 4 x^2$$ ⇒ $$4(x)(x)$$ $$y = x^2 + 5 x$$ ⇒ $$(x)(x + 5)$$ $$y = 2 x^2 + 6 x$$ ⇒ $$2(x)(x + 3)$$ $$y = 2 x^2 -9 x + 9$$ ⇒ $$(2 x -3)(x -3)$$ $$y = 3 x^2 -7 x -6$$ ⇒ $$(3 x + 2)(x -3)$$ $$y = 4 x^2 -x$$ ⇒ $$(4 x -1)(x)$$ $$y = x^2 -3 x -10$$ ⇒ $$(x -5)(x + 2)$$ $$y = x^2 + 3 x$$ ⇒ $$(x)(x + 3)$$ $$y = x^2 -6 x + 8$$ ⇒ $$(x -4)(x -2)$$ $$y = x^2 + 7 x + 10$$ ⇒ $$(x + 5)(x + 2)$$ $$y = 2 x^2 + 3 x$$ ⇒ $$(2 x + 3)(x)$$ $$y = x^2 + 8 x + 15$$ ⇒ $$(x + 5)(x + 3)$$ $$y = 2 x^2 -2 x$$ ⇒ $$2(x)(x -1)$$ $$y = 4 x^2 + x -3$$ ⇒ $$(4 x -3)(x + 1)$$ $$y = 4 x^2 -8 x$$ ⇒ $$4(x)(x -2)$$ $$y = x^2 + 4 x -5$$ ⇒ $$(x + 5)(x -1)$$ $$y = x^2 -4 x -5$$ ⇒ $$(x -5)(x + 1)$$ $$y = 3 x^2 + 8 x -3$$ ⇒ $$(3 x -1)(x + 3)$$ $$y = 2 x^2$$ ⇒ $$2(x)(x)$$ $$y = x^2 -2 x -15$$ ⇒ $$(x + 3)(x -5)$$ $$y = x^2 + 5 x + 6$$ ⇒ $$(x + 2)(x + 3)$$ $$y = x^2 -8 x + 15$$ ⇒ $$(x -5)(x -3)$$ $$y = 3 x^2 -2 x$$ ⇒ $$(3 x -2)(x)$$ $$y = 4 x^2 -x -3$$ ⇒ $$(4 x + 3)(x -1)$$ $$y = x^2 -5 x + 4$$ ⇒ $$(x -4)(x -1)$$ $$y = 2 x^2 -3 x -2$$ ⇒ $$(2 x + 1)(x -2)$$ $$y = x^2 + x -20$$ ⇒ $$(x -4)(x + 5)$$ $$y = x^2 + 4 x -5$$ ⇒ $$(x -1)(x + 5)$$